Kościelne początki Tarnowa - Poniewozik, Leszek (Archiwa, Biblioteki i Muzea Kościelne, 2021)
The article presents the earliest history of the church in Tarnów. The current town of Tarnów was founded on the land of the village of Tarnów Wielki in 1330. The village of Tarnów Mały (now Tarnowiec) was located near the village of Tarnów Wielki. Historical sources from the fi rst half of the fourteenth century mention the existence of the parish of Tarnów without specifying whether it is Tarnów Wielki or Mały. The existing literature has adopted the view that the oldest parish of Tarnów was located at St. Martin Church in the present village of Zawada. As a consequence, the village of Zawada was considered to be originally part of Tarnów Wielki or Mały with the origins going back to the twelfth century, and the Benedictines of Tyniec being perceived as its founders. At the beginning of the fourteenth century Tarnów Wielki and Mały and the surrounding villages became the property of Spycimir, Leliwa coat of arms. He contributed to building, on the outskirts of Tarnów Wielki, a castle and then a chapel, the existence of which has been proved since 1331. It was acknowledged that the chapel had been dedicated to the Assumption of the Virgin Mary and had had the parish rights. In 1330 the town of Tarnów was founded in the village of Tarnów Wielki. After that, the Parish of the Nativity of the Virgin Mary was established in the main square of the town. The parish has been proved since 1346. Recognizing that fact that St. Martin Parish was connected with Tarnów Wielki meant accepting the claim that in about half of the fourteenth century there were three parishes in the town of Tarnów. Finally, in 1400 the Bishop of Cracow, Piotr Wysz created a collegiate church in Tarnów on the basis of the Parish of the Nativity of the Virgin Mary, St. Martin Parish and the castle chapel. The author tried to show in the article that certain parts of the ecclesiastical history of Tarnów have diverged from the truth. According to the literature, St. Martin Parish was connected with Tarnów Mały, which is today Tarnowiec, and the Benedictines should be regarded as its founders. The history of this parish is not so distant. There are no clear source materials which could allow for certainty on this issue, but evidence indicates that it was created in the early thirteenth century. The history of the castle church in Tarnów was also wrongly interpreted. In the light of sources it can be stated that it was dedicated to the Blessed Virgin Mary. The claim that it was dedicated to the Assumption of the Virgin Mary is the result of misunderstanding. That is true that there was the church dedicated to the Assumption of the Virgin Mary in Tarnów, but it was not connected with the castle. The theory that the castle chapel had the parish rights is also erroneous. In fact it was an ordinary castle chapel similar to other chapels of this type.